2021
DOI: 10.1002/pbc.28254
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma

Abstract: Rhabdomyosarcoma is a heterogeneous disease both in presentation and histology. Improvements in a multimodality therapy resulted in the improved overall survival for patients with a low‐risk and intermediate‐risk disease but not for patients with a metastatic disease. We reviewed and contrasted the North American and European practice patterns, though ultimately the principles of staging, surgery, radiation therapy, and chemotherapy are similar in both Children's Oncology Group and International Society of Pae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…38 There has also been a move to reduce the use of radiotherapy in childhood Hodgkin lymphoma, 39 but attempts initiated from 1989 to reduce systematic use of radiotherapy in rhabdomyosarcoma were less successful and it was more frequently used again since 2005. 40 Among children who do receive radiotherapy, increasing numbers have been treated with protons rather than photons. While it is still controversial whether SPTs are less frequent among children treated with protons, a study of more than 1700 patients from a leading proton therapy centre found no evidence of increased risk compared with that following photon radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 There has also been a move to reduce the use of radiotherapy in childhood Hodgkin lymphoma, 39 but attempts initiated from 1989 to reduce systematic use of radiotherapy in rhabdomyosarcoma were less successful and it was more frequently used again since 2005. 40 Among children who do receive radiotherapy, increasing numbers have been treated with protons rather than photons. While it is still controversial whether SPTs are less frequent among children treated with protons, a study of more than 1700 patients from a leading proton therapy centre found no evidence of increased risk compared with that following photon radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of cranial irradiation in first‐line treatment for children with ALL, which began to decrease in the 1990s, has been eliminated 38 . There has also been a move to reduce the use of radiotherapy in childhood Hodgkin lymphoma, 39 but attempts initiated from 1989 to reduce systematic use of radiotherapy in rhabdomyosarcoma were less successful and it was more frequently used again since 2005 40 . Among children who do receive radiotherapy, increasing numbers have been treated with protons rather than photons.…”
Section: Discussionmentioning
confidence: 99%
“…The high-risk rhabdomyosarcoma group includes fusion-positive metastatic patients regardless of age, as well as metastatic fusion-negative or ERMS patients who are 10 years of age or older. It should be noted that there is a lack of international consensus on risk stratification in rhabdomyosarcoma [124].…”
Section: Risk Stratificationmentioning
confidence: 99%
“…RMS cells are similar to skeletal muscle progenitor cells, but they can originate from different types of tissues (3). Histopathological markers have long been used to classify RMS into several clinical subgroups, including embryonal RMS (ERMS), alveolar RMS (ARMS), pleomorphic, and spindle cell and sclerosing RMS (ssRMS) (4,5). The majority of cases, known as ERMS, have a positive prognosis and are associated with a lower risk of metastasis and recurrence (6, 7).…”
Section: Introductionmentioning
confidence: 99%